Entrepreneurship Curriculum Management in Improving Student Financial Literacy in West Java - Sobari, Sobari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
his study aims to analyze the management of the entrepreneurship curriculum in improving the financial literacy of students in West Java. The research uses a qualitative approach with a case study design at three private universities, namely the National University of the Republic of Indonesia (UKRI), the STTT Bandung Polytechnic, and the University of Pasundan (Unpas). Informants are selected purposively and involve academic leaders, study program chairs, lecturers, entrepreneurship program managers, and students. Data was collected through in-depth interviews, observations, and documentation studies, then analyzed interactively through data reduction, data presentation, and conclusion drawn. The results of the study show that the entrepreneurship curriculum has the potential to be a strategic instrument to strengthen students' financial literacy, but its effectiveness depends on the quality of integration at the planning, implementation, and evaluation stages. At the planning stage, the integration of financial literacy is not uniform. At the implementation stage, project-based learning, business simulations, mentoring, and evidence-based feedback have proven to be most effective in shaping applied financial skills. However, at the evaluation stage, financial literacy has not received adequate assessment weight because the rubric still emphasizes creativity, presentation, and promotion. This study concludes that strengthening financial literacy through entrepreneurship education requires a curriculum that explicitly formulates financial competencies, supported by contextual learning, and assessed through standardized authentic assessments.